A study of the intracellular signalling events involved in the zona pellucida-induced acrosome reaction in human spermatozoa - Du Plessis, S. S. (Simon Stephanus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2002.